Advergame: Potential and Prospects for Advertising Strategy - Azaze Azizi Abdul Adis; Hyung, Jun Kim (Universiti Malaysia Sabah, 2016)
This paper aims to discuss the concept of advergames and its benefits from the marketing perspectives and also the future potential of advergames. It suggests that marketing communication by using games, as a medium will result into more effective marketing communication strategy to the brand developer. The concepts of advergames and its types were both discussed. Then, the advantages and disadvantages of using advergames were also explained and how advergames differs compared to other media. Finally, the potential and prospects of advergames that would give opportunities to marketing practitioner completes the discussion of this paper.